The anti-inflammatory and analgesic activities of 2Br-Crebanine and Stephanine from Stephania yunnanenses H. S.Lo - Cui, Lili; Peng, Chaorui; Li, Jun; Cheng, Xin; Fan, Xiao; Li, Jingyu; Yang, Zixian; Zhao, Yuancui; Ma, Yunshu (Frontiers in Pharmacology, 2023)
Ethnopharmacological relevance: Crebanine (Cre) and Stephanine (Step) are isoquinoline aporphine-type alkaloids that are extracted from Stephania yunnanenses H. S. Lo. Plants of the Stephania genus are often used for treatment of stomach pain, abdominal pain, and rheumatoid arthritis. Both Cre and Step exhibit strong activities but are also associated with a certain level of toxicity, 10,11-dibrominecrebanine (2Br-Cre) is a bromine-modified derivative of Cre that we prepared and tested in order to reduce toxicity and enhance efficacy. Aim of this study: To investigate the anti-inflammatory and analgesic effects of 2Br-Cre and Step based on previous research findings and explore the specific biological mechanisms involved. Materials and methods: The anti-inflammatory and analgesic effects of 2Br-Cre and Step were investigated using a range of experimental models, including xylene-induced ear edema, carrageenan-induced pleurisy, carrageenan-induced paw edema, the hot-plate test, the naloxone antagonism test and the acetic acid writhing test. A model of chronic constriction injury (CCI) of the sciatic nerve was also established to investigate therapeutic effects. A RAW264.7 cell model was established using lipopolysaccharide (LPS) to estimate the effects of these compounds on cytokines levels. Results: 2Br-Cre and Step significantly inhibited ear edema, paw edema and presented anti-inflammatory activity in the pleurisy model by inhibiting leukocyte migration and nitric oxide (NO) production, and by reducing the levels of PGE2. 2Br-Cre and Step significantly increased the pain threshold of mice subjected to heat stimulation; the effect was blocked by naloxone, thus suggesting that the analgesic effects of 2Br-Cre and Step were mediated by opioid receptors. 2Br-Cre and Step inhibited the frequency of writhing and prolonged the latency of writhing, and reduced the abnormal increase in the levels of BDNF in the serum and brain, thus alleviating the pain caused by CCI. In addition, 2Br-Cre and Step significantly inhibited the production of several inflammatory cytokines (IL-6, IL-1β and TNF-α) by LPS-induced RAW264.7 macrophages (p<0.01). Conclusion: 2Br-Cre and Step exerted remarkable anti-inflammatory and analgesic effects. As a structural modification of Cre, 2Br-Cre retains the anti-inflammatory and analgesic activity of Cre but with better efficacy. Consequently, 2Br-Cre should be investigated further as a lead compound for analgesia.